Biometric Technologies from the Anthropocentric and Nonanthropocentric Perspective - Baďurová, Barbora; Húšťava Šipulová, Marta (Studia Ecologiae et Bioethicae, 2024)
Biometric technologies or biometrics are becoming widespread, and, in many ways, they help to make human life easier. As this new technology has a significant impact on not just humans but also nonhuman nature, the authors perceive that there is a need of utmost importance to deal with the evaluation of the impact from the point of view of ethics, especially environmental ethics. The article is based mainly on an interdisciplinary approach, namely, a theoretical analysis of biometric technologies from the point of view of the two most significant approaches to argumentation in environmental ethics: anthropocentric and nonanthropocentric. The study will analyze the results of empirical research conducted among consumers in Slovakia in the years (2023-2024). The authors also base the analysis on relevant empirical data, presenting their own research on consumers’ subjective perceptions of the risks and benefits of biometrics. The authors conclude that it is essential to consider subjective and objective anthropocentric arguments and nonanthropocentric arguments for and against biometrics to understand the broader consequences of this technology.